Cost management in bamboo airways Status and solution for the development - Võ, Thị Diệp Anh (2020)
Theoretical: The thesis has systematized the theories on cost management in general and cost management in airline industry Practical:Based on analyzing current state of cost management at Bamboo Airways Joint Stock Company, the author has identified the causes to limitations in the management practices After that, the author has proposed some solutions to overcome, the weaknesses of cost management and contribute for the development of cost, management at Bamboo Airways Joint Stock Company.